TRAFFIC MANAGEMENT FOR SAFE PEDESTRIAN WALK USING SMART TECHNOLOGY - Sharlin M K; Sherin Firuthuba S; Muthumalathi .M (Galaxy International Interdisciplinary Research Journal, 2022)
The traffic management considered as one of the major dimensions of a smart city. This paper is based on Smart Technology is used to predict the traffic density for future to minimize the accident or violation rule it avoid the accident while crossing the road in pedestrian walk. This paper gives a solution and it’s proportional. This system automatically detects without manual errors. If the violation exists, our system will automatically find the vehicle by sending fine fee message to the concern person and display the vehicle number in a LED display board on particular traffic signal. This paper mainly helps to avoid the unnecessary worst traffic disasters.